Sildenafil for improving outcomes in patients with corrected valvular heart disease and persistent pulmonary hypertension: a multicenter, double-blind, randomized clinical trial. (21st December 2017) - Bermejo, Javier; Yotti, Raquel; García-Orta, Rocío; Sánchez-Fernández, Pedro L; Castaño, Mario; Segovia-Cubero, Javier; Escribano-Subías, Pilar; San Román, José Alberto; Borrás, Xavier; Alonso-Gómez, Angel; Botas, Javier; Crespo-Leiro, María G; et al.
Abstract: Aims: We aimed to determine whether treatment with sildenafil improves outcomes of patients with persistent pulmonary hypertension (PH) after correction of valvular heart disease (VHD). Methods and results: The sildenafil for improving outcomes after valvular correction (SIOVAC) study was a multricentric, randomized, parallel, and placebo-controlled trial that enrolled stable adults with mean pulmonary artery pressure ≥ 30 mmHg who had undergone a successful valve replacement or repair procedure at least 1 year before inclusion. We assigned 200 patients to receive sildenafil (40 mg three times daily, n = 104) or placebo ( n = 96) for 6 months. The primary endpoint was the composite clinical score combining death, hospital admission for heart failure (HF), change in functional class, and patient global self-assessment. Only 27 patients receiving sildenafil improved their composite clinical score, as compared with 44 patients receiving placebo; in contrast 33 patients in the sildenafil group worsened their composite score, as compared with 14 in the placebo group [odds ratio 0.39; 95% confidence interval (CI) 0.22–0.67; P < 0.001]. The Kaplan–Meier estimates for survival without admission due to HF were 0.76 and 0.86 in the sildenafil and placebo groups, respectively (hazard ratio 2.0, 95% CI = 1.0–4.0; log-rank P = 0.044). Changes in 6-min walk test distance, natriuretic peptides, and Doppler-derived systolic pulmonary pressure were similar in both groups. Conclusion: Treatment with sildenafil in patients with persistent PH after successfully corrected VHD is associated to worse clinical outcomes than placebo. Off-label usage of sildenafil for treating this source of left heart disease PH should be avoided. The trial is registered with ClinicalTrials.gov, number NCT00862043.